( y + 1 ) 1 / 2 − ( y − 1 ) 1 / 2 = ( 4 y − 1 ) 1 / 2
Find the value of y satisfying the equation above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We have to solve the equation y + 1 − y − 1 = 4 y − 1 . Squaring Both sides
⟹ y + 1 + y − 1 − 2 y 2 − 1 = 4 y − 1 4 ( y 2 − 1 ) = ( 2 y − 1 ) 2 4 y 2 − 4 = 4 y 2 + 1 − 4 y y = 4 5
In this case , The option " There is no solution " is correct
This is incorrect. Once you start squaring both sides of an equation, you run the risk of finding extraneous roots. So you still need to make sure that the final value(s) you have found is indeed correct.
In this case, with y = 4 5 , L H S = y + 1 − y − 1 = 1 . 5 − 0 . 5 = 1 and R H S = 4 y − 1 = 2 . Hence, y = 4 5 cannot be a solution because L H S = R H S .
i think you have to specify which option since the mcq can change the answers position, in my case it was the fifth option that was 'there is no solution'
On squaring, we have,
y+1 + y-1 - 2√(y^2 - 1) =(4y -1),
Or, - 2√(y^2-1) = (2y - 1),
Again squaring, we have,
4(y^2 - 1) = 4y^2 - 4y + 1,
4y = 5, or y = 5/4.
This answer 5/4 is actually an answer to only the last equation, 4y = 5, and not an answer to the original equation for the reason that same answer would be found for the following equations also:
1. - √(y+1) + √(y - 1) = √(4y - 1),
2. +√(y+1) + √(y-1) = √(4y-1),
And the same answer would also be found if the sign is changed from (+) to (- )on the RHS for each of these equations.
As such, on squaring, different equations may become identical and may generate answers which may not satisfy the original equations. Unless the answer obtained satisfies a particular equation, it can not be treated as pertaining to that equation.
As y=5/4 does not satisfy the original equation in the instant case, the original equation does not have any solution.
Problem Loading...
Note Loading...
Set Loading...
Square both sides :- ( y + 1 ) + ( y − 1 ) − 2 y 2 − 1 = 4 y − 1 ⟹ − 2 y 2 − 1 = 2 y − 1
Squaring again gives:-
4 ( y 2 − 1 ) = ( 2 y − 1 ) 2 ⟹ 4 y − 5 = 0 ⟹ y = 4 5
Substituting 4 5 in the eqn, we get:-
R H S : ( 4 9 ) 1 / 2 − ( 4 1 ) 1 / 2 = 1 While L H S comes out to be ( 4 ) 1 / 2 = 2 . Hence x = 4 5 is a extraneous solution obtained due to squaring. Hence No solution .